Foreign Job Opportunities and Internal Migration in Vietnam - Fukase, Emiko (World Bank, Washington, DC, 2013)
This paper investigates the role of employment opportunities created by foreign-owned firms as a determinant of internal migration and destination choice using the Vietnam Migration Survey 2004 and the Vietnam Household Living Standards Survey 2004. Multinomial logit and conditional logit models are estimated to study both origin and destination-specific characteristics of migrants. The paper finds that the migration response to foreign job opportunities is larger for female workers than male workers; there appears to be intermediate selection in terms of educational attainment; and migrating individuals on average tend to go to destinations with higher foreign employment opportunities, even controlling for income differentials, land differentials, and distances between sending and receiving areas.